Determinación de las propiedades físicas y químicas del suelo del lote número 3 de la Universidad Tecnica de Cotopaxi, campus Salache mediante el uso de técnicas básicas de laboratorio de suelos 2023-2024. - Calo Quisaguano, Darwin Fabricio (2024)
The research was carried out in the Soil Laboratory of the Agronomy course of the Faculty of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi, with the objective of analyzing the physical and chemical properties of the soil in a plot of land number 3 of the Technical University of Cotopaxi, Salache Campus, the basic techniques were adapted of the University of Almeria (Spain), which were adapted according to the materials, supplies and equipment available in the University laboratories, Six soil samples were taken to analyze the structure, real density, apparent density, porosity, texture, pH, nutrients, cation exchange capacity and organic matter. For comparison and determination of the percentage of error, a soil sample was sent to the National Institute of Agricultural Research (INIAP), Campus Salache shows a structure of 1.17 mm (slightly stable), real density of 2.58 g/cm3 (low), apparent density 1.39 g/cm3 (medium), porosity of 46,25 % (low), a loam textured soil, pH of 7.91 (moderately alkaline), Na 200 ppm (high), K 899.3 ppm (high), Ca 3406.6 ppm (high), NO3 400 ppm (high), electrical conductivity 1178 dSm-1(high), cation exchange capacity 19.47 meq/100 g (medium) and organic matter of 8010% (high), It is concluded that by means of the results of the soil analysis sent by the National Institute of Agricultural Research (INIAP) and the results obtained in the laboratory analysis practices of the Technical University of Cotopaxi, Campus Salache, similar and reliable results were obtained. Therefore, a guide with 9 basic laboratory techniques is proposed for the analysis of the physical and chemical properties of the soil in the soil laboratory of the Technical University of Cotopaxi, Faculty of Agricultural Sciences and Natural Resources.